Exploring the macroevolutionary impact of ecosystem engineers using an individual-based eco-evolutionary simulation - Smith, TJ; Parry, LA; Dunn, FS; Garwood, RJ (Wiley, 2024)
Ecosystem engineers can radically reshape ecosystems by modulating the availability of resources to other organisms through modifying either physical or biological aspects of the environment. The introduction or removal of ecosystem engineers from otherwise stable ecosystems can impact the diversity of co-occurring species, such as driving local extinctions of native taxa. While these impacts are well established over ecological timescales for a wealth of taxa, the macroevolutionary implications of the onset of ecosystem engineering behaviours are less clear. Despite this uncertainty, ecosystem engineering has been implicated in several major transitions in Earth history including the appearance of extensive bioturbation during the Cambrian substrate revolution and associated Ediacaran–Cambrian turnover, and the Great Oxygenation Event. Whether ecosystem engineers are frequently associated with turnover and extinction in deep time is not known. Here we investigate this with an eco-evolutionary simulation framework in which we assign lineages the ability to impact the fitness of co-occurring taxa through phenotype–environment feedback. We explore numerous conditions, including how frequently such feedback occurs, and whether ecosystem engineers modify or create niches. We show that there is no general expected outcome from the introduction of ecosystem engineers. In a minority of runs, ecosystem engineering lineages completely dominate, rendering all others extinct, but in others they persist (but do not dominate), or die out. We suggest that ecosystem engineers have complex impacts, but possess the capacity to profoundly shape diversity, and it is appropriate to consider them alongside other exogenous extinction drivers in deep time.